Contemporary Ritual Landscapes. Preface to the Special Issue - Pirjo Kristiina Virtanen; Eleonora A. Lundell; Marja-Liisa Honkasalo (Journal of Ethnology and Folkloristics)
This special issue of the Journal of Ethnology and Folkloristics is composed on the basis of papers presented at the Ethnography of Contemporary Ritual Landscapes panel organised at the Conference of the Finnish Anthropological Society at the University of Helsinki, October 21–22, 2015.